Clinical predictors of therapeutic laparotomy in anterior abdominal stab injuries: a multicenter study from low-income institutions in Ethiopia - Segni Kejela; Abel Hedato; Yeabsera Mekonnen Duguma; Meklit Solomon Gebremariam (Journal of Trauma and Injury)
Purpose Despite the high incidence of abdominal stab injuries, the rate of nontherapeutic laparotomies and the predictors of therapeutic laparotomies have rarely been studied in low-income settings. Methods This multicenter retrospective study involved three of the largest academic medical centers in central Ethiopia. All patients who sustained an anterior abdominal stab injury and underwent exploratory laparotomy, regardless of the intraoperative findings, were included over the 3-year course of the study. Results Of the 117 patients who underwent exploratory laparotomy, 35 patients (29.9%) underwent nontherapeutic laparotomies. Three factors predicted therapeutic laparotomy: hollow viscus evisceration (adjusted odds ratio [AOR], 5.77; 95% confidence interval [CI], 1.16–28.64; P=0.032), localized and generalized peritonitis (AOR, 4.77; 95% CI, 1.90–11.93; P=0.001), and white blood cell count ≥11,500/mm3 (AOR, 2.77; 95% CI, 1.002–7.650; P=0.049). The overall positive predictive value of the therapeutic predictors was 80.2%, while the negative predictive value of all predictor-negative patients was 58.1%. The predictors would have prevented 51.4% of the nontherapeutic laparotomies. Conclusions Close to one-third of the patients had a nontherapeutic laparotomy. The clinical predictors of therapeutic laparotomy were shown to have a high positive predictive value despite a lower negative predictive value. Further prospective studies that involve all patients who sustain anterior abdominal stab injuries are needed to potentially improve on the negative predictive value of the predictors suggested by our study.